Indexing and Abstracting Practices in Mbarara University of Science and Technology Library. - Natwijuka, Rabecca (Kabale University, 2024)
The purpose of the study was to assess the impact of indexing and abstracting practices on the success of the Mbarara University of Science and Technology library. The study was guided by four objectives which include identifying the different types of indexes and abstracts at Mbarara University of Science and Technology library, establishing the contributions of indexing and abstracting practices in Mbarara University of Science and Technology library. finding out the challenges facing indexing and abstracting practices in Mbarara University of" Science and Technology library and suggesting possible solutions to the challenges facing indexing and abstracting practices in Mbarara University of Science and Technology library. The study used a descriptive research design. Using simple random and purposive sampling techniques, a total of 50 respondents were selected to participate in the study. Questionnaires. interview guides were the data collection methods used in this study. From the study findings, citation indexes and abstracts by writer were the most common types of indexes and abstracts at the Mbarara University of Science and Technology library. Easy access or information was the most significant contribution of indexing and abstracting practices in the Mbarara University of Science and Technology library. The study findings also revealed that ignorance of using modern technology/ ICT son wares was the biggest challenge facing indexing and abstracting practices in the Mbarara University of Science and Technology library. The study findings revealed that training or all stakeholders was the most possible solution to the challenges facing indexing and abstracting practices in the Mbarara University of Science and Technology library.